The LGU Extension Services in a Major Rice-Growing Area: The Case of Hagonoy, Davao del Sur - Rosa Fe D. Hondrade (Philippine Institute for Development Studies (PIDS), 2007)
The province of Davao del Sur is considered one of the major rice-producing provinces of Region XI. It has been regarded as Mindanaos top rice-yielding province because of its municipalitys (Hagonoy) high yield performance. The study shows that farmers have multiple sources of information within a given farming system. In addition to formal institutions like the national and regional agencies, the provincial and municipal agriculture services of the local government units, farmers seek out or exchange information and knowledge with input suppliers, traders and other private individuals who have stakes in rice production and marketing. Much of the information travels freely but some may also come with a fee. Such stakeholders (public or private) in rice may interact either to fulfill their needs or to pursue their interests. And as they interact with one another, information on prices, market opportunities, new technologies and practices as well as policy changes is also exchanged.
Keywords: 330; agriculture extension; rice-growing area; municipal agriculture services; knowledge management; Reisanbau; Agrarboden; Öffentliche Einrichtung; Mindanao; Philippinen